Factors contributing to the use of conversational silence in academic discourse among Malaysian undergraduate students - Ibrahim, Bashir; Mohd. Kasim, Zalina; Abdullah, Ain Nadzimah; Rafik-Galea, Shameem (UKM Press, 2018)
Asians are said to use silence in academic situation more than other learners from Europe and America. With the increased need for students’ oral participation in the language learning classroom and other academic situations, the Asian silent behavior has been considered a problem. The aim of this study is to investigate factors that contribute to the use of conversational silence by Malaysian science and non-science undergraduate students in academic discourse. Seventeen undergraduate students from a local university in Malaysia participated in a focus group interview which required them to respond to questions related to the beliefs of their culture on the use of silence, the extent to which the participants practice silence in academic discourse, and factors that contribute to the use of conversational silence. There were two groups each from the Departments of English and Computer and Communication System who informed the research. The study was underpinned by Brown and Levinson Politeness Theory, which is tied to the concept of ‘face’ as something that is highly valuable, and must be guarded in interaction. The findings suggest that some factors such as socio-cultural upbringing, personality and intimidation by the environment play a role in the use of silence by the informants of this study.